Relationship Between Small Farmer Cooperative Limited and Women’s Rights in Household Assets - Poudel, Gehanath (Journal of Advanced Academic Research, 2017)
Small Farmer Cooperative Limited (SFCL) is one financial institution worked for the welfare of poor and marginalized people. It mostly focuses on the women empowerment from the socio-economic perspective. The main objective of this study is to explore the relationship between SFCL and women's right in household assets. In Nepalese context, males are known as the head of family and led the every decision in household level activities. The study was conducted in the three Village Development Community of Illam district of Nepal during the time of 2016. In total 522 women participated for the study who was the member of SFCL. The study found the significant difference in women before and after involving in the SFCL. Women said that they felt the many changes in their life. They were able to mobilize the economic resources and aware in the right of women. They could actively participate in the decision of mobilization of household assets. SFCL build the level of confidence and sensitized in the right of information in any activities. Women could raise their voice in-front of any authority and could take leadership in community development activities. It was necessary to continue the SFCL to improve the socio-economic life of community. Journal of Advanced Academic Research Vol. 3, No.3, 2016, page:31-39